Centralising insolvencies of pan-European corporate groups: a creditor's dream or nightmare - Ronen-Mevorach, Irit (Sweet & Maxwell, 2006)
Reflects on whether the EC's centralised approach to corporate insolvency within multinational groups of companies is likely to promote fairness to creditors. Considers the extent to which such a system fulfils creditors' expectations concerning the location of the insolvency process, discourages forum shopping and provides sufficient representation. Details, with reference to cases including the Chancery Division ruling in Re Daisytek-ISA Ltd, how the rights of multinational group creditors may be threatened under Council Regulation 1346/2000 and suggests a potential solution based on identification of a true centre of main interests which would ensure procedural transparency.